Peningkatan Hasil Belajar Ipa Tentang Faktor Penyebab Perubahan Benda Melalui Model Pembelajaran Students Teams Achievement Divisions (STAD) - Krisnowati, Krisnowati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this classroom action research is to improve the science learning result about the factors causing the change of the object through Learning Model of Students Teams Achievement Divisions (STAD) in grade VI students of Semester I SD Negeri Jeblog Karanganom District Klaten Regency Lesson Year 2022/2023. The research was conducted in class VI with 21 subjects of the study conducted in two cycles, each cycle held three meetings, with each cycle each 2 hours of lesson with activities of planning, action, observation, and reflection. Data collection techniques in this study include techniques in the form of written tests and non-test techniques in the form of observation, The results showed there is an enumeration of learning outcomes of IPA which is indicated from the increase of the average acquisition cycle u for 76 there cycle II increased to 82, while the percentage of completeness classical cycle l of 71% cycles rose to 90%, from the observation average of teacher activity cycle l was 85, cycle ll increased to 94 While student activity cycle I was 80% good category, cycle II increased to 93% good category.